Synergy of Actors in Handling Child Violence Cases in Bangkalan Regency - Nugroho, Reka Fitriana; Rodiyah, Isnaini (Universitas Muhammadiyah Sidoarjo, 2021)
This study used descriptive qualitative method. The location of this research was carried out at the Office of Family Planning, Women's Empowerment and Child Protection (DKBP3A) Bangkalan Regency. the technique of determining the informants used purposive sampling technique in determining the informants, namely the Head of the Bangkalan Women's Empowerment and Child Protection (P3A) Division, the Head of the Women and Children Protection Unit (PPA) Bangkalan Police, the Secretary of the Bangkalan Integrated Service Center (PPT), and the Chair of the Children's Forum Organization ( FA) Bangkalan Regency. Data collection techniques using observation techniques, interviews, and documentation. While the data analysis technique uses the components of interactive model data analysis from Miles and Huberman (1992) through data collection, data reduction, data display, conclusions or verification. The results showed that the synergy of actors in handling cases of child violence in Bangkalan Regency was by using 2 indicators of synergy. First, the results of the communication that occurred between the P3A Office and several actors involved in handling cases of child violence in Bangkalan Regency were still not optimal. Second, the coordination between the WUA Office and related actors in handling cases of child abuse in Bangkalan Regency is established in the PPT Coordination Meeting. In the PPT Coordination Meeting, actors related to the protection and handling of violence against children in Bangkalan Regency evaluated the performance of several institutions, found solutions if there were problems during case handling and found new ideas to make Bangkalan a Child Friendly City.